Mengkaji ulang hukum acara perceraian di pengadilan agama - Gofar, Abdullah (IJTIHAD Jurnal Wacana Hukum Islam dan Kemanusiaan, 2013)
Procedural legal issues of religion in resolving divorce cases still using prosedural of civil law (H.I.R andR.B.Bg). Size of formal mechanistic truths, so the more important aspects of the divorce prosess legalcertainty and axpediancy, however, rule out the maslahat aspect, in accordance with the value of Islamiclaw. The research objective is to examine the application of civil law in the process of divorce in westernreligious courts that have shifted, so the procedural law can not be used to answer problems in areas offamily law. Research methodology using normative judicial approach to secondary data laws and judicialdecisions of religion. Procedural law religious marriage in Islamic can not be measurred by mere formalproof, but there are aspects of the sacred reality can not be measured from a mere formal proof.Enforcement of civil law aspect âmutatis mutandisâ, it did not touch the substantial aspects theâmashlahatâ aspect. Implications of the case, that the rule of law in judicial process likely to lead todesecularization religious law of Islamic, not the desration of Islamic law.